PENGARUH KADAR AIR SERASAH KAYU SUNGKAI TERHADAP KEBAKARAN HUTAN DI AREAL IUPHHK-HT PT. AYA YAYANG INDONESIA - Aris Setiawan; Normela Rachmawati (Jurnal Sylva Scienteae, 2021)
This study aims to determine the effect of Sungkai litter water content (Peronema canescens) on forest fires. The benefit of this research is to provide information and input on related institutions to take actions to prevent forest fires. The research object is Sungkai litter in the IUPHHK-HI area of PT. Aya Yayang Indonesia on 26-year-old plants, with 4 treatments and 5 groups. Sampling with the Stratified Random Sampling (layered random) method, data analysis using Randomized Block Design (RCBD). Based on the results of the study note that the largest average water content is in the dense canopy treatment and there is an understorey (29.67%) and a thin canopy treatment there is an understorey (27.07%) then dense canopy there is no understorey (21.80 %) and the treatment with the least water content is thin canopy treatment and no undergrowth (17.30%). The average of all samples of Sungkai litter water content (23.96%) is known to be less than 30% so according to. Ministry of Forestry and Forestry (1999), can be categorized as very vulnerable to forest fires. Based on the Diversity Analysis test, it is known that the treatment has a very significant effect, for the normality test (using Liliefors test) it is known that the data is spread normally while through the Bartlett Variety homogeneity test it is known that the data is homogeneous. Through Honestly Significant Difference test (BNJ) it is known that each treatment has a significantly different effect.Keywords: Kadar air; Serasah; Kebakaran hutan; Sungkai